SUMBER DAYA FITRAH MANUSIA DAN PENGEMBANGANNYA DALAM PERSPEKTIF PENDIDIKAN ISLAM - Iffah Mardliyah; Agus Wedi (AT-TA'DIB: JURNAL ILMIAH PRODI PENDIDIKAN AGAMA ISLAM, 2022)
This research uses this using a descriptive qualitative research approach. Data collection techniques in this study use document analysis. An important source used in this exploration is journals related to the discussion in research. The results of this study show that humans are born into a world with a sacred state, and go through several stages from the stage of the formation of lumps of flesh to the stage of giving reason to humans. While the competence of human fitrah that he has existed since birth into the world, this ability will not develop without education which is one way of developing this potential. Man is both an object as well as a subject in education because the two cannot be separated in unity. The abilities possessed by humans are certainly higher than the abilities possessed by other creatures because humans have advantages that cannot be possessed by other creatures, namely reason